La universidad como agencia del logos (2012)
ABSTRACT: Drawing on Derrida's position regarding the two sides of pharmakon writting –poison and remedy–, from the Platonic tradition, will expand the concept of logos to show how to combine trends that are present in all reality: Eros and thanatos, logos and ananké. From this distinction we will see how University, defined as an agency (and with it the speech and writing), also involves an interplay of forces: being at service of repetition, dogma and the patriarchalism; or at service of creation, criticism as an emancipatory exercise project and the gift as conducive to "us". The road is an ethical decision favors worth reviewing. Reasonableness is proposed here as a viable alternative.